CREATING MODERN CLOTHING DESIGNS FROM UZBEK NATIONAL FABRICS - Ulugboboeva Mavjuda Maripjanovna (Modern American Journals, 2025)
This article discusses the creation of modern clothing designs using traditional Uzbek fabrics that have been produced for centuries across the territory of Uzbekistan. The study highlights the aesthetic, cultural, and technological value of national textiles such as atlas, adras, bekasam, and shoyi, and their reinterpretation in contemporary fashion design. It also explores how traditional weaving patterns, natural dyeing methods, and regional ornamentation are being revived through innovative approaches to garment construction, sustainability, and identity expression. The integration of heritage textiles into modern silhouettes not only preserves national traditions but also enhances the global recognition of Uzbek craftsmanship in the fashion industry.
Keywords: Uzbek national fabrics, atlas, adras, textile design, fashion, cultural heritage, sustainable design, modern clothing.